ANALISIS DAMPAK KEPEMIMPINAN INSTRUKSIONAL KEPALA SEKOLAH TERHADAP PENGEMBANGAN PROFESIONAL GURU SD IIS PSM KEDIRI - Amalia Majid, Fitri; Itsna Rusydiana; Binti Mar’atus Sholikah; Ulfa Nur Azizah; Alfiatu Sholikah (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2022)
Instructional leadership plays a crucial role in the management of educational institutions with the primary goal of enhancing the standards and effectiveness of teaching methods and student academic achievement. This study is designed to explore how principals implement instructional leadership strategies and their impact on the success of the learning process within the school environment. The study suggests that for effective learning to be achieved, it is important for principals to adopt and consistently implement instructional leadership practices. This not only improves the quality of learning in the classroom but also promotes a positive learning culture within the school environment. Keywords: leadership;instructional; teacher professional